Prediction model of gear tooth flank fracture considering interfacial friction - ZHI YanFeng; WANG XiaoPeng; CAO ZhiGang; GUAN HongJie; YU FeiPeng; FAN RuiLi; LI HaiXia; WAN ShaoXiong (Jixie qiangdu)
Under the fatigue loading condition, tooth flank fracture, crack source initiated at the subsurface position, is a subsurface fatigue failure. The failure mode is closely related to the local material strength and local stress state at the internal points of teeth. Based on the contact theory and elastic mechanics, a mathematical model for calculating the internal field stress of gear teeth with interfacial friction and the stress intensity with hardness gradient was established, and the risk prediction of gear tooth flank fracture was carried out. The results show that the calculated maximum stress risk position occurs at a certain depth below the tooth surface, which is basically consistent with the representative position of the tooth surface fracture fatigue source. With the increase of the friction coefficient, the internal safety factor of the gear teeth decreases, which indicates that poor interfacial lubrication can easily lead to the accelerated initiation of internal cracks in the gear teeth, resulting in the fracture fatigue failure of the tooth surface. The risk prediction model provides basic technical guarantee and support for the design and manufacture of tooth flank fracture resistance.